2007
DOI: 10.1074/jbc.m608589200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-mediated Amyloidogenesis and the Promotion of Oxidative Lipid Damage by Amyloid β Proteins

Abstract: Evidence of oxidative stress and the accumulation of fibrillar amyloid ␤ proteins (A␤) in senile plaques throughout the cerebral cortex are consistent features in the pathology of Alzheimer disease. To define a mechanistic link between these two processes, various aspects of the relationship between oxidative lipid membrane damage and amyloidogenesis were characterized by chemical and physical techniques. Earlier studies of this relationship demonstrated that oxidatively damaged synthetic lipid membranes promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
97
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 81 publications
3
97
0
Order By: Relevance
“…1A), derived from cholesterol, and the aldol product of the latter (see 2 in Fig. 1 A) (24), covalently modify A␤ and increase its amyloidogenicity (16)(17)(18)(25)(26)(27). Prior data indicated that cholesterol oxidation products 1 and 2, denoted 1(2) hereafter because they interconvert via an aldol/retro-aldol reaction (16,18,24), react with A␤ via Schiff base formation at the N-terminal ␣-amine of Asp-1 (D1) and the side-chain -amines of Lys-16 (K16) and Lys-28 (K28) (18).…”
mentioning
confidence: 99%
“…1A), derived from cholesterol, and the aldol product of the latter (see 2 in Fig. 1 A) (24), covalently modify A␤ and increase its amyloidogenicity (16)(17)(18)(25)(26)(27). Prior data indicated that cholesterol oxidation products 1 and 2, denoted 1(2) hereafter because they interconvert via an aldol/retro-aldol reaction (16,18,24), react with A␤ via Schiff base formation at the N-terminal ␣-amine of Asp-1 (D1) and the side-chain -amines of Lys-16 (K16) and Lys-28 (K28) (18).…”
mentioning
confidence: 99%
“…Various diseases involve proteins modified by HNE and protein cross-linking through HNE adducts contributes to disease pathogenecities [14,[16][17][18]. Here, we showed that spectrins are the primary targets of HNE, and that HNE-modified spectrins generate irreversibly cross-linked aggregates in human RBCs.…”
Section: Discussionmentioning
confidence: 75%
“…HNE reportedly modifies the three His residues of amyloid β protein (Aβ). These HNE-modified Aβ molecules have an increased affinity for membrane lipids and possess a conformation similar to that of mature amyloid fibrils [16,25]. The observed enrichment of HNE-His adducts (Fig.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations